Halogen Bearing Amphiboles, Aqueous Fluids, and Melts in Subduction Zones: Insights on Halogen Cycle From Electrical Conductivity. Issue 3 (25th March 2021) - Manthilake, G.; Koga, K. T.; Peng, Y.; Mookherjee, M.
Abstract: Amphiboles are hydrous minerals that are formed in the oceanic crust via hydrothermal alteration. The partial substitution of halogens for OH − makes amphibole one of the principal hosts of Cl and F in the subducting slab. In this study, we investigated the electrical conductivity of a suite of halogen bearing amphibole minerals at 1.5 GPa up to 1, 400 K. The discontinuous electrical behavior indicates dehydration of amphibole at ∼915 K. This is followed by dehydration induced hydrous melting at temperatures above 1, 070 K. We find that the released aqueous fluids have an electrical conductivity of ∼0.1 S/m. This high electrical conductivity is likely to explain anomalously high electrical conductivity observed in certain subduction zone settings. This high electrical conductivity of an order of magnitude greater than the electrical conductivity of pure aqueous fluids at similar conditions is likely due to the partitioning of the F and Cl into the aqueous fluids. We also noted that subsequent to the dehydration, secondary phases form due to the breakdown of the primary halogen bearing amphibole. Chemical analyses of these secondary phases indicate that they are repositories of F and Cl. Hence, we infer that upon dehydration of the primary halogen bearing amphibole, first the F and Cl are partitioned into the aqueous fluids and then the halogens are partitioned back to the secondary mineral phases. These secondary minerals are likely to transport the halogen to the deep Earth and may in part explain the halogen concentration observed in ocean island basalt. Plain Language Summary: Amphiboles are one of the principal mineral phases that accommodate halogens in the subducting slab. The aqueous fluid released during the dehydration of amphibole dissolves and transfers halogens into the overlying wedge mantle. The resulting fluid exhibits high electrical conductivity. Our study also indicates that a significant portion of F and small quantities of Cl carried by amphibole are partitioned back to the secondary mineral phases that result from the breakdown of the primary amphibole. These secondary mineral phases are likely to transport halogen into the Earth's interior and may explain the distinct halogen contents observed between lower mantle‐derived ocean island basalts compared to MORB sources. Key Points: The presence of F and Cl increases the electrical conductivity in aqueous fluids During dehydration, a fraction of F and Cl partitions into solid phases F and Cl can be transported to the deep mantle by secondary minerals